Recessive hypophosphataemic rickets, and possible aetiology of the 'vitamin D-resistant' syndrome. Issue 5 (May 1976) - Stamp, T C; Baker, L R
Abstract : Two out of 3 children of a first-cousin marriage presented with severe rickets in infancy and are now adult. Their disease has shown continued activity, marked resistance to treatment with vitamin D, early fusion of cranial sutures, greatly increased bone density, nerve deafness, and life-long hypophosphataemia unaffected by treatment. Both parents and a third sib were normal clinically and biochemically. Blood grouping supported both stated paternity and parental consanguinity. Genetics of this unique disease can only be explained satisfactorily on the basis of autosomal recessive transmission, a mode not previously reported in primary hypophosphataemia. This homozygous disease resembles an exaggerated form of common X-linked rickets, though it is caused by a different gene. Although rare, it is particularly important because of the information it provides on the pathogenesis of both forms. We propose that both syndromes may result from multiple target organ unresponsiveness to 1, 25-dihydroxycholecalciferol in intestine, kidney, bone, and parathyroid gland.